Gross Anatomical Description and CT Scan of the Dromedary Paranasal Sinuses - Bitsha‐Kitime Dieudoné Kabkia; Lobna Ouertani; Ali Lamari; Germain Nissao Magnibo; Abdelmonem Ben Khalifa (Veterinary Medicine and Science)
ABSTRACT Ten dromedary heads, aged between 12 and 18 months, were used to study the anatomy of the paranasal sinuses. The main aim of this work is to provide a detailed and comprehensive description of the anatomy of the dromedary paranasal sinuses and associated structures. By combining Computed Tomography (CT) scans and macroscopic anatomical sections, our study aimed to develop a CT atlas, accompanied by a 3D reconstruction of the healthy sinuses. The anatomical study of the dromedary paranasal sinuses was carried out using fenestrations and transverse anatomical sections and allowed us to study the location and the exact extent of each of these sinuses, as well as the topography and communication between the different sinus compartments. In our CT study, 19 images were obtained, enabling identification of the sinuses, associated deep structures and their communications. Thus, in the dromedary, the frontal sinus was very extensive in the frontal bone, divided into left and right sinuses, each frontal sinus being subdivided into cavities by numerous septa of variable size and position. The ventral conchal sinus was absent, and the maxillary sinus was single and not compartmentalised. The reconstructed 3D model was compared with anatomical sections to validate the accuracy of the observations. In view of these results, we propose to continue the CT study with a larger sample in order to assess variations according to breed or age and sex.